Marketing Strategy for Culinary MSMEs in Magelang City During the Covid-19 Pandemic - Nining Yulia Putri; Ivo Novitaningtyas (Jurnal Pemasaran Kompetitif, 2021)
The Covid-19 pandemic had an impact on MSMEs sectors in Magelang City, one of them is culinary sector. The purpose of this study was to identify and describe the business condition of culinary MSMEs in Magelang City during the Covid-19 Pandemic, and also propose marketing strategy based on a SWOT analysis and marketing mix. This study used descriptive qualitative approach. Primary data were obtained from 30 samples of culinary MSMEs through interview and observation. Data were analyzed based on statistic descriptive to describe the business condition and SWOT to propose the marketing strategy. The results recommend culinary MSMEs in Magelang city to improve product quality and product innovation, provide discounted prices, promote products through social media, and provide venues that comply with health protocol standards. By implementing this marketing strategy, it is hoped that culinary MSMEs in Magelang city business will survive and can develop during the Covid-19 pandemic.